Manila bibliotheca an integrated library-museum ecosystem as a cultivation for accessible spaces for learning and culture - Camposano, Rhodievie Chrystell A.; Ruby Teresa M. de Leon (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Education should be a right for every person, as it holds power that can give them immense number of opportunities that can change their lives for the better holistically. However, in a third world country like the Philippines, quality basic education is quite a hard thing to grasp especially for our less fortunate brethren as they are trapped by circumstances that leave them without spaces to develop their skills, cultivate self-worth, or dream beyond their limitations-- it is quite a predicament for them to focus on just their education. Hence, the idea that educational support spaces and the advanced technology may be merged to serve as a public institution. Through the rapid development of technology, educational support spaces may serve as a hive for students, as well as the general public, whereas they may be able to enrich themselves through inviting environments that can offer solace and a refreshing change of scenery.

In this comprehensive design project, the idea of using artificial intelligence responsibly will be translated into a place where people can comingle and cowork, providing an accessible space for every person who needs a safe space that can provide them with their basic needs to support their education. This new library-museum ecosystem aims to provide any user not only with the chance to improve oneself, but also to improve one's ability to foster human connection
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Museum architecture; Artificial intelligence; Libraries -- Space utilization; Libraries -- Use studies; Library architecture; Joint occupancy of buildings